The Effect of Sharia Finance Socialization and Education on PublicInterest in Using Sharia Banking Services - Helma Maraliza (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the influence of Islamic finance socialization and education on public interest in using Islamic banking services. Involving 66 respondents in two major cities in Indonesia, this study uses a survey method with questionnaires to collect data that measures respondents' perception and understanding of Islamic finance principles, such as profit-sharing and the prohibition of usury. Data analysis using SPSS shows that socialization and education of Islamic finance have a significant positive influence on the increase in public interest in using Islamic banking services, where more than 65% of respondents reported an increase in interest after participating in the socialization and education program. These findings indicate that effective education strategies are very important in communicating Islamic finance concepts in order to build public understanding and trust. The implication of this study is the need for Islamic banks and financial institutions to continue to strengthen Islamic financial socialization and education programs to expand public access to sharia-based financial services. This step not only supports the growth of the Islamic banking sector, but also strengthens sustainable financial inclusion in Indonesia.